Benefícios da aspiração manual intrauterina associada ao uso do misoprostol via vaginal nos casos de abortamento retido - Leal, Nelson Fernandes (2013)
Abortion is an issue that raises discussions in contemporary society, since it involves perceptions of dignity, life, ethics, religion, moral values, women’s rights, and gender. Misoprostol is a low cost drug widely available in hospitals, which makes it accessible. The uterotonic qualities and cervical ripening capacity of misoprostol have made it a drug widely used for many indications in Reproductive Health, including induced labor and incomplete abortion. Manual Intrauterine Aspiration has been used worldwide as a safe and effective alternative to uterine curettage. This procedure is recommended by the World Health Organization and the International Federation of Gynecology and Obstetrics for the treatment of abortion and for cases of termination of pregnancy, as established in current Brazilian legislation.This study aimed to evaluate the benefits of Manual Uterine Aspiration associated to misoprostol in cases of missed abortion. To achieve this proposal, a retrospective study was carried out in a Maternity School, after being approved by the Research Ethics Committee of Assis Chateaubriand Maternity School, under Protocol No. 111/11, from 2010 to 2011. This is an exploratory, cross-sectional, retrospective study with quantitative approach. Regarding the classification, the higher incidence of abortion occurred in the age group of 20-29 years, corresponding to 50.5% of total cases. We verified that the average gestational age was of 8.87 weeks. When comparing the doses of misoprostol used in the study, we observed that the group that received a 400µg dose presented the average age of 27.36 ± 7.18 years, as for the group that received an 800μg dose, the average age was 19.8 ± 2.86 years. Thus observing a statistically significant difference between the average ages of the two groups as regards to the dose, demonstrating that the younger group needed a higher dose to complete the abortion. There was a linear trend between the time interval between administration of misoprostol associated with manual intrauterine aspiration and age, i.e. as the age increases, the time interval decreases and vice versa, which represents a significant difference between time interval and age. The results show that, in the population studied, the Manual Intrauterine Aspiration associated with the use of misoprostol in 400μg and 800μg doses was effective in inducing and curettage of missed abortion in hospital.